Augustine in Byzantium - Lössl, Josef (The journal of ecclesiastical history, 2000)
As Cornelius Mayer wrote recently, the massive output of literature on Augustine (c. 50,000 extant titles) cannot hide the fact that ‘much scholarly work remains to be done on the enormous variety and scope of Augustine's influence’. One area of which this is particularly true is Augustine's impact on Byzantine theology. While Augustine's own use of Greek patristic literature and contacts with the Greek patristic world have been investigated for some time and in some detail, his influence on Greek authors – especially during the later Byzantine era – has been sadly neglected. However, recent research on such authors as Maximos Planudes (c. 1255–1305), Gregory Palamas (1296–1359) and Prochoros Kydones (c. 1333–c. 1370) has done something to remedy that situation. This paper seeks to present a summary of that development and provide a context for further study.